Analisis Pelaksanaan Usaha Pertambangan Batu Gamping Dalam Upaya Pengendalian Kerusakan Lingkungan - Hasmita Hasmita; La Ode Santiaji Bande; Sitti Wirdhana Ahmad (Universitas Halu Oleo, 2019)
This study aimed to know how the impacts of the implementation of the rock mining business (limestone) were and to know the efforts for controlling the environmental damage were conducted by the mining businesses in North Moramo Sub-District, South Konawe District. This research is located in North Moramo Sub-District, South Konawe District, in the Sanggula Village and Mekarjaya Village with case studies at CV. Watu Moramo, CV. Bintang Mas Sukses, and PT. Mekarjaya Moramo. The time of this study held in october to december 2018. The type of this research is a qualitative-descriptive with the Analysis Method of the Data uses the Process Hierarchy Analysis (AHP). The results of this study indicated that the priority vectors of physical impacts of the rock mining business caused dust, roads damage, noise, and increation of the vehicle flow. The priority vectors of social economic and public health impacts caused health problems (ISPA) for the community, created new jobs, and increased their incomes, but some people thought that their incomes have declined and some people lost their jobs. The priority vectors of the environmental management efforts conducted by the mining businesses was watering dust, creating new jobs for the local community, and providing social assistance, and closing the transportation trucks tub. Keywords: Positive and Negative Impacts, Mining Business, Limestone, Environmental Management.